Antioxidant and Antibacterial Activities of Hydrolysate Chitooligosacharides in Crab Shell (Portunus Pelagicus) from Degradation of Chitosanase, α-Amylase, Lipase and Cellulase Enzymes - Amellia, Siska; Rosida, Dedin Finatsiyatull (Swiss German University & Perhimpunan Penggiat Pangan Fungsional dan Nutrasetikal Indonesia (P3FNI), 2023)
The crab shell (Portunus pelagicus) has many benefits, one of the benefits is the used in the manufacture of chitooligosaccharides. The crab shell was chosen because it contains 20- 30% chitin inside. Chitin can be processed into chitosan and then hydrolyzed into chitooligosaccharides using enzymes. This study aims to determine the type of enzyme that is effective in the process of hydrolyzing chitooligosaccharides with various enzymes are the α-amylase, lipase, cellulase, chitosanase and a combination of enzymes are chitosanase α-amylase, chitosanase lipase, and cellulase chitosanase. The observation data were analyzed using ANOVA. The results showed that the best chitooligosaccharides obtained resulting from the hydrolysis of a combination of cellulase chitosanase enzymes which had the best characteristics, namely the highest degree of deacetylation of 94.95%, the lowest molecular weight of 3.54 KDa, the antioxidant activity of the DPPH method was 5.21 ( µmol TE/g), the FRAP antioxidant method was 2.27 (µmol TE/g), the diameter of the inhibition area (DDH) was 7.30 mm in Staphylococcus aureus bacteria and 15.9 mm in Salmonella typhosa bacteria. From these results, it can be known that this chitooligosaccharide is more effective in inhibiting the growth. The Gram-positive bacteria was compared to gram-negative bacteria.